Blended Learning dalam Pembelajaran Agama Islam pada Pandemi Covid-19 - Riya Irawan; Slamet Mujiono; Oky Ristya Trisnawati (IAINU Kebumen, 2023)
ABSTRACTThis study aims to determine the implementation of blended learning in PAI learning at SMK N 1 Kebumen during the Covid-19 Pandemic and the impact of blended learning in PAI learning in class 10 AKL 3 and 4 at SMK N 1 Kebumen during the Covid-19 pandemic. This study uses a qualitative method. Data collection techniques using observation, interviews and documentation. Technical analysis of data using data reduction, data presentation and draw conclusions. The implementation of blended learning in PAI learning at SMK N 1 Kebumen uses two systems, namely online and offline systems. The implementation of online learning is carried out using WhatsApp as a medium in learning Islamic religious education because it makes it easier for students to learn and collect assignments. The implementation of offline learning is carried out face-to-face and in the classroom, taking into account health protocols. Offline learning, each class is divided into 2 groups, namely group A and group B, the learning system shifts once a week alternating between online and offline learning. The implementation of blended learning provides a new paradigm, namely learning is no longer centered on the teacher, but more focused on the learner. The impact of implementing blended learning on students includes triggering student activity and participation in learning, where students are allowed to explore a wider range of learning through other media, not only focusing on the teacher and existing books. Keywords: Blended Learning, Islamic Religious Education, Covid-19 Pandemic